1999
DOI: 10.1144/0050645
|View full text |Cite
|
Sign up to set email alerts
|

The Paleocene deepwater sandstone play West of Shetland

Abstract: Following the discovery of oil in Paleocene sandstones in the Foinaven and Schiehallion fields in 1992 and 1993, exploration in the Faeroe-Shetland Basin has been very active. Most of the basin has been covered with 3D seismic surveys and numerous wells have been drilled for the Paleocene deep water play. However, success in terms of commercial discoveries has been limited. Detailed analysis suggests that the Foinaven/Schiehallion geological setting is unique in terms of hydrocarbon charge history, reservoir q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
124
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(131 citation statements)
references
References 19 publications
7
124
0
Order By: Relevance
“…Cretaceous' reflector shown by Lamers & Carmichael (1999;their Ritchie et al (1996) can be identified locally in 205 individual basins/sub-basins (e.g. Goodchild et al 1999;Grant et al 1999;Larsen et al 206 2010), though widespread identification and regional correlation at formation level remains 207 ambiguous.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Cretaceous' reflector shown by Lamers & Carmichael (1999;their Ritchie et al (1996) can be identified locally in 205 individual basins/sub-basins (e.g. Goodchild et al 1999;Grant et al 1999;Larsen et al 206 2010), though widespread identification and regional correlation at formation level remains 207 ambiguous.…”
mentioning
confidence: 99%
“…Although these coarse clastic rocks 319 are generally assumed to have been deposited in 'deeper' water than those of the Victory 320 Formation (e.g. Ritchie et al 1996;Lamers & Carmichael 1999;Harker 2002), the evidence 321 for this assumption is equivocal (see Discussion).…”
mentioning
confidence: 99%
See 3 more Smart Citations